De novo renal cell carcinoma in a kidney allograft treatment with percutaneous radiofrequency ablation: a case report - Paškonis, Marius; Andreika, Laimutis; Andreika, Linas; Jurgaitis, Jonas; Jankevičius, Feliksas; Strupas, Kęstutis (Lietuvos chirurgija, 2015)
The incidence of malignant tumors in renal allograft recipients is higher than in the general population. Kidney carcinomas represent 4.8% of the tumors in transplant patients. Only 10% of them occur in the transplanted kidney. Graft tumors can be transmitted by donors, metastases from the recipient’s native organs, or de novo development after transplantation. The mean time to diagnosis of the tumor after transplantation is 10 years. We report the case of a 45-year old male patient with an incidental locally confined 15 mm renal cell carcinoma detected in allograft kidney’s lower pole 16 years after the transplantation. The patient successfully underwent a minimally invasive procedure - percutaneous radiofrequency ablation, completely eliminating the tumor and preserving graft function with no signs of early complications. One year after the procedure, there is no evidence of oncological disease recurrence or late complications and the patient maintains an adequate graft function with no need for hemodialysis.